2014
DOI: 10.1183/09031936.00025513
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage cytology resembles sarcoidosis in a subgroup of granulomatous CVID

Abstract: have recently became commercially available for noninvasive measurements [3]. These developments can be helpful to further explore the role of neonatal lung function in the development of respiratory diseases in later life. @ERSpublications Impaired neonatal lung function is associated with life respiratory symptoms; its measurement at birth is important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…We perform broncho-alveolar lavage, prior to biopsy, to exclude infection. It has been suggested that GLILD may be associated with a BAL lymphocytosis (>20%) in the majority of patients [52,53] , but whether further analysis of cells retrieved at BAL is able to avoid surgical biopsy has yet to be properly examined. The CD4/CD8 preponderance has varied between studies, and a higher ratio has been associated with a more favourable prognosis in terms of lung function decline in one study [53] , but not in another [54] .…”
Section: Figure 5: Histology Of Glild Demonstrating a Polymorphous Inmentioning
confidence: 99%
See 1 more Smart Citation
“…We perform broncho-alveolar lavage, prior to biopsy, to exclude infection. It has been suggested that GLILD may be associated with a BAL lymphocytosis (>20%) in the majority of patients [52,53] , but whether further analysis of cells retrieved at BAL is able to avoid surgical biopsy has yet to be properly examined. The CD4/CD8 preponderance has varied between studies, and a higher ratio has been associated with a more favourable prognosis in terms of lung function decline in one study [53] , but not in another [54] .…”
Section: Figure 5: Histology Of Glild Demonstrating a Polymorphous Inmentioning
confidence: 99%
“…It has been suggested that GLILD may be associated with a BAL lymphocytosis (>20%) in the majority of patients [52,53] , but whether further analysis of cells retrieved at BAL is able to avoid surgical biopsy has yet to be properly examined. The CD4/CD8 preponderance has varied between studies, and a higher ratio has been associated with a more favourable prognosis in terms of lung function decline in one study [53] , but not in another [54] . It is recognised that abnormalities present in blood lymphocyte populations in CVID may also be present in BAL [55] , but in general there is a paucity of data on lung lymphocyte populations in CVID One study [53] included an assessment with trans-bronchial biopsy but this was not adequate to make a firm diagnosis in over 2/3 of patients.…”
Section: Figure 5: Histology Of Glild Demonstrating a Polymorphous Inmentioning
confidence: 99%
“…Both CVID and sarcoidosis may show an increased CD4/CD8 ratio at bronchoalveolar lavage cytology. However, the ratio is more pronounced in sarcoidosis where 3.5 and 4.0 are considered as cut‐off points …”
Section: Discussionmentioning
confidence: 99%
“…However, the ratio is more pronounced in sarcoidosis where 3.5 and 4.0 are considered as cutoff points. 3,20,24 Sarcoidosis is usually associated with increased levels of Ig, ACE, chitotriosidase, vitamin D and calcium. On the other hand, CVID shows decreased levels of Ig, vitamin D, calcium, switched B-memory, although raised levels of ACE may be documented.…”
Section: Discussionmentioning
confidence: 99%
“…A restrictive profile at PFTs is observed with reduced carbon monoxide diffusion capacity (D LCO ) [43]. Bronchoalveolar lavage (BAL) is useful for investigating infections, while GLILD has been associated with BAL lymphocytosis (>20%) with a variable CD4/CD8 ratio [37,44]. Granulomatous disease frequently affects the liver, spleen, and skin [37,38,39].…”
Section: Lung Manifestations In Common Variable Immunodeficiencymentioning
confidence: 99%